Endoscopic Treatment of Idiopathic Subglottic Stenosis: A Systematic Review - Lavrysen, Emilie; Hens, Greet; Delaere, Pierre; Meulemans, Jeroen (Frontiers in Surgery, 2020)
Purpose: to identify different endoscopic techniques for treatment of idiopathic subglottic stenosis (iSGS) and evaluate treatment results. Methods: Embase and Cochrane Library were searched for publications on endoscopically treated iSGS. Identified interventions included procedures with cold knife, dilation (rigid or balloon) or laser (CO2 or Nd:YAG), used in several combinations and supplemented with mitomycin C and/or corticosteroid. Primary endpoint was time interval between successive endoscopic procedures. Secondary endpoints were stenosis recurrence rate, total number of interventions per patient during follow-up, tracheotomy rate and rate of open surgery. Results: Eighty-six abstracts were reviewed and 15 series were included in the analysis. Mean sample size was 57 subjects (range 10 – 384, σ 90.84) and mean age was 47 years (range 36 – 54, σ 4.45). Time interval ranged from 2 to 21 months (weighted mean (WM): 12). Rate of stenosis recurrence ranged from 40% to 100% (WM: 68%). Mean amount of interventions per patient varied between 1.8 and 8.3 (WM: 3.7). Tracheotomy rate varied between 0% and 26%, (WM: 7%) and rate of open surgery varied between 0% and 27% (WM: 10%). Single modality CO2 lasering showed highest rate of recurrence, highest amount of interventions and shortest time interval. Combined techniques generated overall better outcomes. Conclusions: A multitude of endoscopic techniques are being used for treating iSGS, all with a considerable recurrence rate. In this review, no superior modality could be identified. Consequently, endoscopic management could be considered a valuable primary treatment option for iSGS, but open surgery still plays an important role.